Estrategias didácticas y su incidencia en el aprendizaje significativo de las matemáticas de los estudiantes de séptimo año de la escuela “Capitán Moroni” cantón Quevedo, año lectivo 2023 – 2024. - Luis Fernando Naranjo Guzmán (2024)
The teacher faces the challenge of promoting meaningful learning in students. Every day, you must employ effective teaching strategies to demonstrate high-quality education. Therefore, the objective of this research is to analyze the impact of teaching strategies and their impact on the meaningful learning of mathematics in seventh grade students atthe "Capitán Moroni" School of Cantón Quevedo during the 2023-2024 school year. The nature of the research combines qualitative and quantitative approaches, including a literature review and field research conducted at school. An exploratory research was applied to understand the pedagogical practices of the teaching sector and its influence on meaningful learning, while through a descriptive research it was possible to analyze the characteristics of the teaching strategies used by teachers. The techniques of interviewing the manager and surveys of teachers and students allowed the collection, organization, processing, analysis and interpretation of the information. This field work was carried out with 1 director, 3 teachers and 56 seventh grade students of the institution.This research managed to determine how teaching strategies affect meaningful learning based on the critical nodes in teaching practice obtained from the results of the diagnosisof the current situation, the development of a teacher training plan on the application of teaching strategies was proposed. innovative in the teaching of mathematics that will allow the improvement of student learning